2019
DOI: 10.3322/caac.21573
|View full text |Cite
|
Sign up to set email alerts
|

Tools to facilitate communication during physician‐patient consultations in cancer care: An overview of systematic reviews

Abstract: Tools have been developed to facilitate communication and support information exchange between people diagnosed with cancer and their physicians. Patient‐reported outcome measures, question prompt lists, patient‐held records, tape recordings of consultations, decision aids, and survivorship care plans have all been promoted as potential tools, and there is extensive literature exploring their impact on patient outcomes. Eleven systematic reviews of studies evaluating tools to facilitate patient‐physician commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 45 publications
(321 reference statements)
2
45
0
1
Order By: Relevance
“…While patients do re‐establish their relationship with GPs after completion of chemotherapy (Brennan, Butow, Marven, Spillane, & Boyle, 2011; Lang et al., 2017), our research identified the importance of a highly engaged, motivated and well‐informed GP for rural patients to be cared for at the EOL in their own community. Patients’ clinical and social needs could be better identified through the routine use of tools to facilitate physician–patient communication in cancer care, including EOL care (Licqurish et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While patients do re‐establish their relationship with GPs after completion of chemotherapy (Brennan, Butow, Marven, Spillane, & Boyle, 2011; Lang et al., 2017), our research identified the importance of a highly engaged, motivated and well‐informed GP for rural patients to be cared for at the EOL in their own community. Patients’ clinical and social needs could be better identified through the routine use of tools to facilitate physician–patient communication in cancer care, including EOL care (Licqurish et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The health care system has increased efforts to provide more patient-centered care by customizing care to individual patient's needs [21,22]. Thus, understanding what matters most to patients is unique and of significant value.…”
Section: Discussionmentioning
confidence: 99%
“…Question prompt lists (QPL) to facilitate question-asking behavior of patients and patient-reported outcome measures (PROMs) to facilitate better insight into patients' well-being and needs have turned out to be effective in improving clinician-patient communication in oncology, leading to favorable patient outcomes. [52][53][54][55] QPLs and PROMs designed to encourage patients to express their perceptions, needs, and preferences regarding their doctors' empathic communication might increase clinicians' awareness as to how they are perceived and how they could optimize their use of empathy. Future research could focus on the possibility of designing a tool to help elicit emotional needs of patients with focus on clinicians' empathy use in advanced cancer consultations and investigate its potential to improve patient-perceived empathy and ultimately patient outcomes.…”
Section: Practical Implicationsmentioning
confidence: 99%